SUMOylation of ROR-γt inhibits IL-17 expression and inflammation via HDAC2. Issue 1 (December 2018) - Singh, Amir; Khare, Prashant; Obaid, Abeer; Conlon, Kevin; Basrur, Venkatesha; DePinho, Ronald; Venuprasad, K.
Abstract Dysregulated ROR-γt-mediated IL-17 transcription is central to the pathogenesis of several inflammatory disorders, yet the molecular mechanisms that govern the transcription factor activity of ROR-γt in the regulation of IL-17 are not fully defined. Here we show that SUMO-conjugating enzyme Ubc9 interacts with a conserved GKAE motif in ROR-γt to induce SUMOylation of ROR-γt and suppress IL-17 expression. Th17 cells expressing SUMOylation-defective ROR-γt are highly colitogenic upon transfer to Rag1–/– mice. Mechanistically, SUMOylation of ROR-γt facilitates the binding of HDAC2 to the IL-17 promoter and represses IL-17 transcription. Mice with conditional deletion of HDAC2 in CD4+ T cells have elevated IL-17 expression and severe colitis. The identification of the Ubc9/ROR-γt/HDAC2 axis that governs IL-17 expression may open new venues for the development of therapeutic measures for inflammatory disorders. Interleukin-17 (IL-17)-secreting CD4 T cells (Th17) are induced by the master transcription factor RORγt, and are important for anti-fungal immunity and inflammatory responses. Here the authors show that Ubc9-mediated SUMOylation of RORγt induces HDAC2 binding to IL-17 promoter for suppressing IL-17 production in Th17 cells.